Periodontal inflammation is associated with increased circulating levels of endothelial progenitor cells: a retrospective cohort study in a high vascular risk population - María Vázquez-Reza; Antía Custodia; Iria López-Dequidt; Marta Aramburu-Núñez; Daniel Romaus-Sanjurjo; Alberto Ouro; João Botelho; Vanessa Machado; Ramón Iglesias-Rey; Juan Manuel Pías-Peleteiro; Rogelio Leira; Juan Blanco; et al. (SAGE Publishing, 2023)
Background: One of the main biological mechanisms behind the link between periodontitis and atherosclerotic vascular diseases is vascular endothelial dysfunction. Particularly, circulating endothelial progenitor cells (EPCs) have been considered a biomarker of altered vascular endothelial function. Objectives: The aim of this study was to investigate relationship between periodontal inflammation and increased number of circulating EPCs. Design: This is retrospective cohort study. Methods: In this study, 85 elderly patients with a previous history of hypertension were followed up to 12 months. A baseline full-mouth periodontal assessment was carried out, and the amount of periodontal tissue inflamed per subject was calculated as a proxy of periodontal inflammation [periodontal inflamed surface area (PISA)]. The number of circulating EPCs (CD34 + /CD133 + /KDR + ) was determined by flow cytometry from peripheral blood samples collected at baseline and 12 months. Results: Mean concentrations of CD34 + /CD133 + /KDR + progenitor cells were higher in periodontitis patients than in those without periodontitis at baseline [55.4, 95% confidence interval (CI) = 20.8 to 90.0 versus 27.2, 95% CI = 13.6 to 40.8, p  = 0.008] and 12 months (114.6, 95% CI = 53.5 to 175.7 versus 19.1, 95% CI = 10.8 to 27.4, p  = 0.003). A significant increase over the follow-up was noticed in the group of subjects with periodontitis ( p  = 0.049) but not in the nonperiodontitis group ( p  = 0.819). PISA was independently associated with CD34 + /CD133 + /KDR + EPCs at baseline ( B coefficient = 0.031, 95% CI = 0.005 to 0.058; p  = 0.021). The relationship between PISA and CD34 + /CD133 + /KDR + EPCs at 12 months was confounded by increased baseline body mass index ( B coefficient = 0.064, 95% CI = −0.005 to 0.132; p  = 0.066). Conclusion: Periodontal inflammation is associated with high number of CD34 + /CD133 + /KDR + EPCs, thus supporting a potential link between periodontitis and endothelial dysfunction.